2022
DOI: 10.1021/acs.chemmater.2c00615
|View full text |Cite
|
Sign up to set email alerts
|

Circumventing Thermodynamic Constraints in Nucleation-Controlled Crystallization of Al2TiO5-Based Chemical Vapor Deposition Coatings

Abstract: Nucleation is a fundamental part in most syntheses of ceramic materials. Yet, few techniques enable control of this step, which would offer possibilities to attain full-scale kinetic selectivity of the syntheses to reach novel compounds with unique properties. Herein, we present a nucleationcontrolled crystallization pathway to synthesize coatings of aluminum titanate (Al 2 TiO 5 )renowned for its low-to-negative thermal expansionat significantly reduced temperatures than conventional solid-state techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 101 publications
4
12
0
Order By: Relevance
“…72,73 This is also corroborated by the performed peak fitting, shown in Figure S9 in the Supporting Information, where any potential contribution of Ti 3+ is practically negligible. Since we have previously established the co-formation and crystallization of Al 6 Ti 2 O 13 and Al 16 Ti 5 O 34 in the annealed samples by X-ray diffraction, 21,23 we can conclude that Ti 3+ is not likely a structural entity belonging to any of these phases. Thus, Al 6 Ti 2 O 13 and Al 16 Ti 5 O 34 are independent phases with unique Al−Ti stoichiometries.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…72,73 This is also corroborated by the performed peak fitting, shown in Figure S9 in the Supporting Information, where any potential contribution of Ti 3+ is practically negligible. Since we have previously established the co-formation and crystallization of Al 6 Ti 2 O 13 and Al 16 Ti 5 O 34 in the annealed samples by X-ray diffraction, 21,23 we can conclude that Ti 3+ is not likely a structural entity belonging to any of these phases. Thus, Al 6 Ti 2 O 13 and Al 16 Ti 5 O 34 are independent phases with unique Al−Ti stoichiometries.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…, density, structure, composition). , Therefore, given a uniform (homogeneous) chemical composition of our amorphous coatings, a single crystalline phase should be expected to arise during the phase transition; namely, the phase whose stoichiometry is closest to the overall composition of the amorphous layer. , Nonetheless, previous examinations have revealed that a significant co-formation of Al 6 Ti 2 O 13 and Al 16 Ti 5 O 34 also happens even when the Al–Ti ratio in the coating is close-to-ideal (1.93) with respect to the Al 2 TiO 5 ’s stoichiometry ( i.e. , 2–1). , This infers a possibility for compositional fluctuations to be the main reason for the co-formation of Al 6 Ti 2 O 13 and Al 16 Ti 5 O 34 . Indeed, such compositional variations and elemental enrichments are a typical deviation from CNT and have frequently been reported in the crystallization of many glass-forming materials. …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations